(untitled) (Eurasian Research Bulletin, 2022)
The article discusses the epics of Khorezm, their uniqueness, and the styles of performance by bakshi and khalfas. The study of Uzbek folklore in the 20th century, in particular, the study of Khorezm epics, the publication of the Khorezm series of epics "Ashiqnoma" is given. effective research on Uzbek epics by professor Safarboy Rozimboyev, a folklorist scientist, is analyzed. It is stated that folklore samples should be preserved as unique intangible cultural heritage.